PUSAT KOMUNITAS TUNANETRA KOTA BANJARMASIN - Sari, Rizki Maulina; Huzairin, Muhammad Deddy (UNIVERSITAS LAMBUNG MANGKURAT, 2021)
Oftentimes, we happen to meet with blind and visually impaired people in the middle of Banjarmasin City either while begging for some cash, tried to sell some newspaper, singing or more familiar with busking using musical instrument even though sometimes they also used speaker and any other additional instruments or offers massage service with a patch-up looking presentation. The reality that was just explained happen to be one of the situation where a lot of times were under spotlight due to the lack of diversity and also inclusivity in human resource development for blind and visually impaired people. Some of the reasons why difabel people struggled in developing the human resources inside individual is because the lack of facility in public spaces most likely in mobility side, spaces for improvement for individual or also groups for doing organization that can help regularity within the activity inside.